2003
DOI: 10.1097/01.sap.0000044147.09310.e8
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing Function in Patients Who Underwent Hemiglossectomy: Comparison of Primary Closure and Free Radial Forearm Flap Reconstruction With Videofluoroscopy

Abstract: The swallowing function of patients who had undergone hemiglossectomy with either primary closure of the defect or radial forearm flap reconstruction was studied with videofluoroscopy. Patients with primary closure were unable to lift the tongue tip, had poor tongue-to-palate contact on initiating swallowing, had premature spilling of the bolus into the pharynx, had a large amount of barium stasis on the floor of the mouth, and had prolonged oral transit time. With flap reconstruction, patients easily could li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…6 A distinction was further made between tongue defects of 66 percent (group B1) and 75 percent (group B2) in group B, whereas most authors would classify them into subtotal tongue defects. 8,12,23,26,30,37,49 The additional division between groups B1 (66 percent resected) and B2 (75 percent resected) allowed further refinements in flap selection. For group B2 defects, the small amount of remaining tongue (approximately 25 percent) probably has no functional role but plays an important part in maintaining the anatomical integrity of the base of the tongue, the retromolar Plastic and Reconstructive Surgery • December 2010 trigone, or one side of the pterygoid fossa, depending on its location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A distinction was further made between tongue defects of 66 percent (group B1) and 75 percent (group B2) in group B, whereas most authors would classify them into subtotal tongue defects. 8,12,23,26,30,37,49 The additional division between groups B1 (66 percent resected) and B2 (75 percent resected) allowed further refinements in flap selection. For group B2 defects, the small amount of remaining tongue (approximately 25 percent) probably has no functional role but plays an important part in maintaining the anatomical integrity of the base of the tongue, the retromolar Plastic and Reconstructive Surgery • December 2010 trigone, or one side of the pterygoid fossa, depending on its location.…”
Section: Discussionmentioning
confidence: 99%
“…Our results for swallowing, speech function, and aesthetic appearance compare favorably with other studies. 8,24,26,27,36,54,55 …”
Section: Discussionmentioning
confidence: 99%
“…Adequate flap design permits the appropriate degree of closure without sacrificing tongue movement [34,35,36,37,38,39,40,41]. Some comparative studies have indicated no difference in swallow function after reconstruction with either a radial forearm free flap or a pedicled pectoralis major flap [18], while others have shown that the ability to swallow in patients reconstructed with free flaps is superior to that of patients reconstructed with pectoralis major myocutaneous pedicled flaps [42,43,44]. Nevertheless, swallow function is still impaired after resection and free flap reconstruction.…”
Section: Swallowing Function After Surgery For Cancer Of the Head Andmentioning
confidence: 99%
“…Regarding the volume of the flap for the defects of hemiglossectomy, there was some reports that discuss whether the reconstruction with flap is necessary or not [10,11], but most papers describe that reconstruction with free flap provide good functional results [1][2][3][4][5][6][7][8][9]. The flaps seen in these papers are comparatively large, and the size of reconstructed tongues is as large as that of original tongue.…”
Section: Discussionmentioning
confidence: 99%